"Care and feeding": the Asian environmental tobacco smoke consultants programme. (24th November 2004) - Assunta, M; Fields, N; Knight, J; Chapman, S
Abstract : Study objective: To review the tobacco industry's Asian environmental tobacco smoke (ETS) consultants programme, focusing on three key nations: China, Hong Kong, and Malaysia. Methods: Systematic keyword and opportunistic website searches of formerly private internal industry documents. Main results: The release of the 1986 US Surgeon General's report on second hand smoke provoked tobacco companies to prepare for a major threat to their industry. Asian programme activities included conducting national/international symposiums, consultant "road shows" and extensive lobbying and media activities. The industry exploited confounding factors said to be unique to Asian societies such as diet, culture and urban pollution to downplay the health risks of ETS. The industry consultants were said to be "…prepared to do the kinds of things they were recruited to do". Conclusions: The programme was successful in blurring the science on ETS and keeping the controversy alive both nationally and internationally. For the duration of the project, it also successfully dissuaded national policy makers from instituting comprehensive bans on smoking in public places.